Modelo Peru : A Mobile Money Platform Offering Interoperability towards Financial Inclusion - Del Carpio Ponce, Paola Elvira (International Finance Corporation, Washington, DC, 2018)
Like most emerging markets, Peru suffers from low banking penetration and faces challengesto providing financial services. Beginning in 2015, a strategy called Modelo Peru emerged as acollaboration between financial institutions, telecom companies, and the government, with the goalof launching a mobile money platform to better serve the nation’s unbanked and underbanked. Theplatform’s main innovative feature is interoperability among these three groups to achieve scale and breed competition among e-money issuers. Yet after two years the project continues to struggle to align all involved financial institutions toward its development objective, as well as ramp up the number and value of transactions the mobile platform handles. Important challenges to success include investing in a wider distribution network that more effectively reaches the unbanked, and building a strong digital ecosystem that makes the platform relevant and understandable to users. These challenges require better collaboration from the parties involved as well as strong political will. Absent those, mobile financial services in Peru will remain an alternative financial service rather than a tool for financial inclusion.